Medical student confidence when training for a female genitourinary exam using models and standardized patients. Issue 6 (10th March 2022) - Rutledge, Mallory; Link, Kelsey; Zapata, Isain; Carter, Susan
Abstract: Aim: The purpose of this study is to investigate what factors make students feel confident and competent when performing a female genitourinary exam (FGUE) with normal, nonpathologic findings. We anticipated that students would increase their confidence and perceived competence from the first year to the second year of medical school, would prefer the use of specialized standardized patients (SSPs) over models, and that the results would vary by student demographics. Methods: Student confidence and perceived competence were measured using voluntary survey methods pre‐ and postinterventions. Interventions were defined as learning the FGUE on models alone for first‐year medical students and learning the FGUE on SSPs with prior experience using models for second‐year students. Survey responses were evaluated via generalized linear mixed models for numeric responses. Results: The results demonstrated that first‐ and second‐year medical students of racial and ethnic minorities rated themselves as more confident and competent than Caucasian counterparts, which was in many cases more extensive than the effect of an additional year of medical education. Students felt that using SSPs alone was the best mode of learning the exam than either models alone or the combination of models and SSPs. Students' current specialty of choice did not correlate with increased confidence or perceived competence. Conclusion: This study highlights how cultural differences have an impact on confidence and perceived competence in medical students as they prepare for performing a procedure as intimate to the patient as the FGUE.